2005
DOI: 10.1165/rcmb.2004-0335oc
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Axonemal Dynein Light Chain 1 in Primary Ciliary Dyskinesia Patients

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder characterized by chronic infections of the upper and lower airways, randomization of left/right body asymmetry, and reduced fertility. The phenotype results from dysfunction of motile cilia of the respiratory epithelium, at the embryonic node and of sperm flagella. Ultrastructural defects often involve outer dynein arms (ODAs), that are composed of several light (LCs), intermediate, and heavy (HCs) dynein chains. We recently showed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…1B). Overall, TbLC1 is 46.1% identical to CrLC1, including conservation of all residues proposed to bind ␥HC and p45, the only other protein known to interact with LC1 (Horvath et al, 2005;Sakato and King, 2004). Additionally, both of the basic residues believed to make ionic contact within the ATP-hydrolyzing site of the motor domain are conserved in TbLC1 (Sakato and King, 2004).…”
Section: Resultsmentioning
confidence: 91%
“…1B). Overall, TbLC1 is 46.1% identical to CrLC1, including conservation of all residues proposed to bind ␥HC and p45, the only other protein known to interact with LC1 (Horvath et al, 2005;Sakato and King, 2004). Additionally, both of the basic residues believed to make ionic contact within the ATP-hydrolyzing site of the motor domain are conserved in TbLC1 (Sakato and King, 2004).…”
Section: Resultsmentioning
confidence: 91%
“…For nNO validation studies at six (non-UNC) sites, PCD was confirmed by PCD-specific ciliary EM defects and, by the presence of biallelic mutations in PCD genes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Informed consent was obtained at the University of North Carolina at Chapel Hill and collaborating institutions under the auspices of Committees on the Protection of the Rights of Human Subjects.…”
Section: Original Researchmentioning
confidence: 99%
“…In addition, X-linked PCD is occasionally caused by RPGR or OFD1 mutations associated with retinitis pigmentosa or mental retardation, respectively [Vandorp et al, 1992;Zito et al, 2003;Iannaccone et al, 2003;Krawczynski and Witt, 2004;Moore et al, 2006;Budny et al, 2006]. Several other genes have been investigated as candidates for PCD, with negative results [Pennarun et al, 2000[Pennarun et al, , 2002Maiti et al, 2000;Bartoloni et al, 2001;Neesen et al, 2002;Zariwala et al, 2004;Horvath et al, 2005]. A homozygous mutation in the dynein HC DNAH11 (MIM] 603339) has recently been associated with situs inversus and immotile respiratory cilia that have a normal axonemal ultrastructure [Bartoloni et al, 2002].…”
Section: Introductionmentioning
confidence: 99%